(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
The present research focused on the propensity of Venezuelan literary criticism on the reading and study of his contemporary novels, based on the theory of Fredric Jameson (1986), on the interpretive tendencies of long narrative in the countries of the "Third World”. This approach responds to the need to dilute the controversy raised by various authors such as Doris Sommer (2004), Miguel Gomes (2010), Vicente Lecuna (2012), Cecilia Rodríguez Lehmann (2011) and Pedro Luis Vargas Álvarez (2013), on the character of the novels in Latin America; finding a critical framework that oscillates between the rejection of said theory and the acceptance with commercial fines by others.